If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -1) + 2y = 8 Reorder the terms: (-1 + y) + 2y = 8 Remove parenthesis around (-1 + y) -1 + y + 2y = 8 Combine like terms: y + 2y = 3y -1 + 3y = 8 Solving -1 + 3y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3y = 8 + 1 Combine like terms: -1 + 1 = 0 0 + 3y = 8 + 1 3y = 8 + 1 Combine like terms: 8 + 1 = 9 3y = 9 Divide each side by '3'. y = 3 Simplifying y = 3
| Ln(x^7)-ln(x^4)=3 | | -7-18x+9x=0 | | 7(x-1)=-2x+65 | | 4x+5(4-5x)=-22 | | 2p^2=-21p-40 | | 7x-2(5+4x)=8 | | 3x+27=5x+7 | | -5+6(a-3)= | | 18+2p=8p-13 | | 31-6x=3x+17 | | 9-10x=164-45x | | 4-6x-6x=-104 | | 3y-7=9-y+6 | | 28x=24x+24x+4 | | 6x+11=-21-10x | | 2e+20=4e-12 | | 116-6x=3x+17 | | 3x+(x+5)=-11 | | 6(1+8b)-7b= | | -20=5x-7x-8 | | 7(y-7)+4y=-2(y+5) | | 4x-7=2x+7 | | 2uy-5u-uy-2u= | | 0.33(6+9y)=5y-20 | | 5(6x+2)=100 | | 6n-3n+6=6n-2 | | 5x+29=15x-81 | | 6(x+3)+54=-3x | | 21-7x=5x-3 | | 3x+7=32 | | 2x^2+3=10 | | -1-5x=-1 |